KESALAHAN BERBAHASA PADA PENULISAN POSTINGAN DI MEDIA SOSIAL INSTAGRAM - Sinta Noviana; Atiqa Sabardila (Universitas Warmadewa, 2023)
This article aims to identify language errors in Instagram posts. The source of data in this study is posts on social media Instagram. The data in this article are words, phrases, and sentences contained in posts on Instagram. The data collection method used is descriptive qualitative. The technique used in retrieving data is by reading and taking notes from what has been found in Instagram posts. The results in this article are errors in the use of spelling and punctuation, morphology, and syntax. The errors in the use of spelling and punctuation found were errors in the use of periods (.), commas (,), hyphens (-), capital letters, and question marks (?). The errors found in the morphological field were the use of repeated words, capital letters in all words and word abbreviations, not in accordance with PUEBI, word writing, and prepositions. In the field of syntax, the errors found were the use of redundant words and unclear sentences. The conclusion obtained is that in writing posts on Instagram there are still many language errors. Keywords: language errors; social media; Instagram posts